Mafhūm Mahārah al-Istimā‘ fī Kitāb al-Istimā‘ wa al-Hiwār Funūn al-Muqābalah al-Miṡāliyah - Fitria, Hanna Sajida; Setyorini, Dwichandra; Ibrahim, Andi Hazrah Nurhaliza; Urwati, Nursyahidatul; Yuristira, Afif Naufal Andrean (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This research aims to uncover and analyze the concept of listening skills as presented in the book, employing a descriptive-analytical approach. This study employs a qualitative research approach using content analysis. The research data consist of information, concepts, and ideas contained in the book Al-Istimā‘ wa al-Ḥiwār: Funūn al-Muqābalah al-Mithāliyyah, which serves as the primary data source. The data were collected through library research, which involved thoroughly examining the book's content and gathering relevant supporting literature. The collected data were then analyzed using content analysis techniques, which involved identifying, categorizing, and interpreting the emerging themes within the book, thereby producing a comprehensive understanding in line with the study's focus. The results show that the concept of listening skills in this book includes full attention, understanding meaning in context, sensitivity to verbal and non-verbal messages, and the ability to respond appropriately. This book also emphasizes the importance of listening as a basis for building effective and ethical communication, particularly in the context of interviews. This research concludes that this book not only presents theories related to listening skills but also provides applicable strategies that support the development of communication skills in various educational, social, and professional contexts.